Transcriptional dysregulation causes altered modulation of inhibition by haloperidol. (December 2016) - Brady, Lillian J.; Bartley, Aundrea F.; Li, Qin; McMeekin, Laura J.; Hablitz, John J.; Cowell, Rita M.; Dobrunz, Lynn E.
Abstract: Many neuropsychiatric and neurodevelopmental disorders such as schizophrenia and autism involve interneuron transcriptional dysregulation. The transcriptional coactivator PGC-1α regulates gene expression in GABAergic interneurons, which are important for regulating hippocampal network activity. Genetic deletion of PGC-1α causes a decrease in parvalbumin expression, similar to what is observed in schizophrenia postmortem tissue. Our lab has previously shown that PGC-1α −/− mice have enhanced GABAergic inhibition onto CA1 pyramidal cells, which increases the inhibition/excitation (I/E) ratio, alters hippocampal circuit function, and impairs hippocampal dependent behavior. The typical antipsychotic haloperidol, a dopamine receptor antagonist with selectivity for D2-like receptors, has previously been shown to increase excitation in the CA1 region of hippocampus. We therefore tested whether haloperidol could normalize the I/E balance in CA1 of PGC-1α −/− mice, potentially improving circuit function and behavior. Surprisingly, we discovered instead that interneuron transcriptional dysregulation caused by loss of PGC-1α alters the effects of haloperidol on hippocampal synaptic transmission and circuit function. Acute administration of haloperidol causes disinhibition in CA1 and decreases the I/E ratio onto CA1 pyramidal cells in slices from PGC-1α +/+ mice, but not PGC-1α −/− mice. The spread of activity in CA1, assessed by voltage sensitive dye imaging, is increased by haloperidol in slices from PGC-1α +/+ mice; however haloperidol decreases the spread of activity in slices from PGC-1α −/− mice. Haloperidol increased the power of hippocampal gamma oscillation in slices from PGC-1α +/+ mice but reduced the power of gamma oscillations in slices from PGC-1α −/− mice. Nest construction, an innate hippocampal-dependent behavior, is inhibited by haloperidol in PGC-1α +/+ mice, but not in PGC-1α −/− mice, which already have impaired nest building. The effects of haloperidol are mimicked and occluded by a D2 receptor antagonist in slices from PGC-1α +/+ mice, and the effects of blocking D2 receptors are lost in slices from PGC-1α −/− mice, although there is no change in D2 receptor transcript levels. Together, our results show that hippocampal inhibitory synaptic transmission, CA1 circuit function, and hippocampal dependent behavior are modulated by the antipsychotic haloperidol, and that these effects of haloperidol are lost in PGC-1α −/− mice. These results have implications for the treatment of individuals with conditions involving PGC-1α deficiency. Highlights: Haloperidol causes disinhibition in hippocampus mediated by dopamine D2 receptors. This decreases the I/E ratio and enhances circuit activity but impairs behavior. Haloperidol's effects are lost in PGC-1α −/− mice, and circuit function is altered. Haloperidol restores γ oscillation power in PGC-1α −/− slices, which was enhanced. Transcriptional dysregulation alters haloperidol's effects on hippocampal function.